A Supported Pd2 Dual‐Atom Site Catalyst for Efficient Electrochemical CO2 Reduction. Issue 24 (6th May 2021) - Zhang, Ningqiang; Zhang, Xinxin; Kang, Yikun; Ye, Chenliang; Jin, Rui; Yan, Han; Lin, Rui; Yang, Jiarui; Xu, Qian; Wang, Yu; Zhang, Qinghua; Gu, Lin; et al.
Abstract: Dual‐atom site catalysts (DACs) have emerged as a new frontier in heterogeneous catalysis because the synergistic effect between adjacent metal atoms can promote their catalytic activity while maintaining the advantages of single‐atom site catalysts (SACs), like 100 % atomic utilization efficiency and excellent selectivity. Herein, a supported Pd2 DAC was synthesized and used for electrochemical CO2 reduction reaction (CO2 RR) for the first time. The as‐obtained Pd2 DAC exhibited superior CO2 RR catalytic performance with 98.2 % CO faradic efficiency at −0.85 V vs. RHE, far exceeding that of Pd1 SAC, and coupled with long‐term stability. The density functional theory (DFT) calculations revealed that the intrinsic reason for the superior activity of Pd2 DAC toward CO2 RR was the electron transfer between Pd atoms at the dimeric Pd sites. Thus, Pd2 DAC possessed moderate adsorption strength of CO*, which was beneficial for CO production in CO2 RR. Abstract : A supported Pd2 dual‐atom site catalyst (DAC) was synthesized and used for electrochemical CO2 reduction reaction (CO2 RR). It exhibited superior CO2 RR catalytic performance with 98.2 % CO faradic efficiency at −0.85 V vs. RHE, far exceeding that of Pd1 SAC, and coupled with long‐term stability.